Strategy of Islamic Religious Education Teachers in Overcoming Moral Decadence at State Middle School 45 Surabaya - Ananda, Rasta; Bakhruddin, Muhammad; Hadi, Muhammad Fazlur Rahman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Islamic Education (PAI) teachers have the responsibility to guide students to be able to provide a positive influence to their students. This is necessary to avoid moral decadence that can affect not only the development of individual students but also the school environment and society. This study aims to examine the strategies used by Islamic Religious Education teachers in dealing with moral decadence of students at SMP Negeri 45 Surabaya. Data collection was carried out through interviews, observations, and documentation to obtain comprehensive information about the strategies implemented by teachers. The results of the study showed the impact of implementing Islamic Religious Education teacher strategies in preventing moral decadence values in students, including, students' insight into moral decadence increases, students' character education becomes stronger, empathy and social awareness are formed, and attitudes of sympathy and empathy between students increase.